Presence of Heavy Metals in Selected Edible Termite Species in Relation to their Surroundings - Kapaale, Meekness (JOOUST, 2022)
Consumption of edible termites has over the years remained undiminished. Termites are among the most consumed insect species in the world. Despite the significance of termites as food, currently published data on the presence and levels of metals compared to nutritional composition in other edible insects is limited. Therefore, this study aimed at assessing heavy metal content in the selected edible termite species in relation to their surroundings in Magoye and Stateland farming blocks in Mazabuka district, southern province of Zambia. The first part involved laboratory analysis to assess heavy metals namely; Copper, Cobalt, Lead, Manganese, Nickel, Zinc and Iron in soil and edible termites. In each camp site termite mounds/nests were purposively identified and selected in triplicates, soil and termite samples were collected. The data was subjected to Chi-square test, analysis of variance (ANOVA) and comparison of means using Least Significant Difference; Post hoc test. The second part involved conducting a survey among 362 purposively selected farmers to determine human activities conducted in the study area. Heavy metals concentration analysis showed soil samples having all metals with Manganese having the highest concentration of 7.707 mgL-1 and termites showed all heavy metals detected in soils excluding Nickel and Cobalt with Iron having the highest concentration of 10.81 mgL-1. The identified genera of termites in the study area were Macrotermes, Amitermes, Odontotermes, Pseudacathotermes and Microtermes. ANOVA showed significant difference with p values in Cobalt (0.000), Manganese (0.000), Zinc (0.007) and Nickel (0.012) and Post hoc test revealed which camp sites were significantly different in the study areas in soil samples. ANOVA showed no significant difference in heavy metal concentrations in all termite samples. There was also no significant Pearson Correlation between heavy metals in soil and heavy metals in termites. Bioaccumulation Factor (BF) for metals showed iron having the highest (BF) of 12.05 at Munjile A in Amitermes. Heavy metals concentration in termites were within the internationally accepted concentration levels The survey results revealed that farmers in Magoye and Stateland practiced more of mixed farming, fertilization activities, pesticide and herbicide application, transportation, milling, mining and burning of residue after harvest. Chi-square test of independence revealed a strong significant relationship between education levels and usage of pesticides (X2 = 24.171; d.f. = 5; p = 0.000) and a significant relationship between the size of land and use of pesticides (X2 = 10.671; d.f. = 3; p = 0.014). Further studies on accumulation of heavy metals in termites should be carried out in other ecological regions in Zambia.
Keywords: Termites; Heavy Metals; Bioaccumulation; Magoye; Mazabuka; Zambia